PENGENALAN PEMANFAATAN EKSTRAK SERAI WANGI SEBAGAI PESTISIDA ORGANIK DI DESA BOCEK KARANGPLOSO MALANG - Ardika Nurmawati; Ika Nawang Puspitawati; Ika Favia Anggraeni; Dendy Wahyu Raditya; Novan Sandhi Pradana; Erwan Adi Saputro (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Bocek Village, located in Karangploso District, Malang Regency, is one of the villages known for its chili production. However, the production of chili plants in this village is often affected by diseases caused by pests such as the fungus Colletotrichum spp., which will cause anthracnose (Patek) disease. This disease can cause defects in chili, reducing the quality of chili production. The farmers have handled the handling by using chemical pesticides, which are considered less effective and harm the environment. One solution that can be used is to use extracts from the citronella to be used as organic pesticides. This community service activity aims to introduce organic pesticides with citronella oil as raw material to the Tri Rejeki farmers group in Bocek Village. The socialization activity was carried out using the lecture method with the material covering the introduction of pesticides, the difference between chemical and organic pesticides, extraction of essential oils with a simple method, and the production process of organic pesticides with citronella oil. An evaluation of the participants was also carried out through a questionnaire given before and after the socialization. After the socialization was conducted, participants understood more about organic pesticides and how to produce them